Transformations of the Dislocation Structure of Nickel Single Crystals - Alferova (Alfyorova) E. A. Ekaterina Aleksandrovna; Lychagin D. V. Dmitry Vasilievich; Lychagina L. L.; Tsvetkov N. A. (2017, 2017)
Title screen